Pendampingan Kegiatan Pembibitan Padi Sistem Dapog di Bumdes Sosrohbahu Desa Rejeni Kabupaten Sidoarjo - Muhammad Muharram; Supandji Supandji (Kadiri University, 2022)
Rejeni Village has a Village Business Unit (Bumdes) named SOSROBAHU with ten members. The Bumdes runs several business units in various fields. The central business unit of Bumdes Sosrobahu is the agricultural sector, namely a production input shop and rice planting services using a Transplanter. The number of farmers in Rejeni Village is also quite large, around 247 farmers, with the main commodity being rice. In the socialization program activities, the implementing team held discussions to explore the problems, namely: The lack of knowledge of farmers about the tray system of rice nurseries, the seeds produced by farmers' seedlings are often yellow, often experience root breakage when planted, have not used suitable planting media for tray system rice nurseries. This Community Partnership Program offers several approach methods to help solve existing problems. The results of the activities in Rejeni Village can save the cost of producing a seedling container/tray IDR4,500,000.00.Rejeni Village has a Village Business Unit (Bumdes) named SOSROBAHU with ten members. The Bumdes runs several business units in various fields. The central business unit of Bumdes Sosrobahu is the agricultural sector, namely a production input shop and rice planting services using a Transplanter. The number of farmers in Rejeni Village is also quite large, around 247 farmers, with the main commodity being rice. In the socialization program activities, the implementing team held discussions to explore the problems, namely: The lack of knowledge of farmers about the tray system of rice nurseries, the seeds produced by farmers' seedlings are often yellow, often experience root breakage when planted, have not used suitable planting media for tray system rice nurseries. This Community Partnership Program offers several approach methods to help solve existing problems. The results of the activities in Rejeni Village can save the cost of producing a seedling container/tray IDR4,500,000.00.